MELACAK BIAS GENDER DALAM PENAFSIRAN KEMENTERIAN AGAMA RI PADA AL-QUR’AN SURAH AN-NISA DAN AL-BAQARAH - Nur Laili Nabilah Nazahah Najiyah; Abdul Hamid; Asa Ade Muliana (Pusat Studi Gender dan Anak (PSGA), Universitas Islam Negeri Syarif Hidayatullah, 2022)
Abstract. Gender bias is an injustice in the division of positions and roles between men and women. Factors that cause bias are the values and norms of society which tend to limit women's space for movement. These understandings of gender bias often get support from patriarchal readings of the Qur'an. Therefore, this research specifically presents a gender-biased form of interpretation of Qur'anic verses in the Interpretation of the Ministry of Religion of the Republic of Indonesia. These verses are QS. an-Nisa: 34 and QS. al-Baqarah: 282. There are two formulations of the problem that are discussed in this study, namely first, what is the nature of the concept of gender bias; and second, the form of gender bias in the interpretation of the book of commentary